2006
DOI: 10.1038/sj.ijo.0803286
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of exercise for treating overweight in children and adolescents: a systematic review

Abstract: Background: Overweight prevalence among children/adolescents is increasing, while adult obesity may potentially cause a decline in life expectancy. More exercise is uniformly recommended, although treatment efficacy remains unclear. Objective: To determine the efficacy of exercise alone for treating overweight in children/adolescents. Design: A systematic review and meta-analysis of randomized trials published in English were completed following multiple database searches performed on December 10, 2004. Studie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
163
0
19

Year Published

2007
2007
2015
2015

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 195 publications
(193 citation statements)
references
References 97 publications
(199 reference statements)
9
163
0
19
Order By: Relevance
“…Nevertheless, comparative studies in adults have shown that the effect of PA on weight control is limited and generally lower than that obtained by diet restriction. [80][81][82][83][84][85] Moreover, it has been established that the relative effectiveness of diet or PA depends upon the degree of adiposity excess, given the maximal effect of diet in markedly obese subjects and that of PA at low degrees of fat excess. 86 In order to disentangle the concept that diet and PA have comparable effects in obesity management, we depicted in Figure 1 how their relative roles should be considered different, keeping body composition into consideration.…”
Section: Role Of Pa In Childhood Obesitymentioning
confidence: 99%
“…Nevertheless, comparative studies in adults have shown that the effect of PA on weight control is limited and generally lower than that obtained by diet restriction. [80][81][82][83][84][85] Moreover, it has been established that the relative effectiveness of diet or PA depends upon the degree of adiposity excess, given the maximal effect of diet in markedly obese subjects and that of PA at low degrees of fat excess. 86 In order to disentangle the concept that diet and PA have comparable effects in obesity management, we depicted in Figure 1 how their relative roles should be considered different, keeping body composition into consideration.…”
Section: Role Of Pa In Childhood Obesitymentioning
confidence: 99%
“…154,155 Lots of research has shown comparable short 144,151 and longterm effects on weight reduction 140,149 in treatment of fatty liver to many other medical and surgical modalities. 148,156,157 Lifestyle interventions delineate the first step in the management of children with NAFLD. However, the longterm impact of the treatment on the disease course remains unclear.…”
Section: Weight Lossmentioning
confidence: 99%
“…Entretanto, intervenções como a prática de atividade física têm levado a resultados discordantes: alguns estudos randomizados têm demonstrado que a prática de incorporar exercícios físicos parece ser mais efetiva em pro-mover perda de peso a longo prazo em crianças com excesso de peso, do que aquela de apenas incorporar orientações dietéticas 15,16,17 . Entretanto, não existe um consenso em relação a esses achados 18 .…”
Section: Introductionunclassified